Financial contagion analysis in frontier markets: Evidence from the US subprime and the Eurozone debt crises - Mothi, Wahbeeah (2020)
This study assesses the effects of the US financial and the Eurozone debt crises on a large set of frontier stock markets. Detrended Cross Correlation Analysis (DCCA) and Detrended Moving Cross Correlation Analysis (DMCA) are employed to investigate whether correlations between the crises-originating countries’ stock markets (US and Greece) and frontier stock markets increased from the calm to each crisis periods. Our results indicate that this was indeed the case and frontier markets were affected by both crises. DCCA and DMCA coefficients increased significantly for countries in Europe and also, although not so strongly, for Middle Eastern ones with the subprime crisis. In the case of the Eurozone debt crisis, the most affected countries were Slovenia, Romania, Nigeria, Kuwait, Oman and Vietnam. Evidence of contagion, using the test proposed by Guedes et al. (2018a, 2018b), is thus weaker in the case of the European debt crisis, leading to the conclusion that frontier stock markets were more affected by the US financial turmoil.